P321 CASE REPORT AND LITERATURE REVIEW: THE HAPPINESS FOR ITALY'S VICTORY AT THE EUROPEAN SOCCER CHAMPIONSHIPS COSTS AN "HAPPY HEART SYNDROME". (18th May 2022) - Fazzini, L; Caggiari, L; Raffo, A; Spissu, M; Contini, F; Pittau, R; Montisci, R
Abstract: Patient Presentation: A 52 y/o female with history of arterial hypertension, diabetes mellitus, Bentall's previous intervention, presented to emergency department complaining dyspnea and oppressive chest pain which arose during celebrations for Italy's victory at the European soccer championship. According to increase in cardiac troponin level and ECG findings of subendocardial ischemia she was admitted to our Coronary Care Unit for acute coronary syndrome suspicious. Management: transthoracic echocardiography (TTE) showed reduced left ventricle ejection fraction (LVEF 37%) with apical and left ventricle medium segments akinesis associated with basal segments hyperkinesis with typical apical ballooning aspect. According to these findings, Takotsubo syndrome (TTS) suspicious overtook acute coronary syndrome. Despite low probability of coronary disease, she underwent coronary angiography which was normal. Eight days later, TTE showed completely recovery with normal LVEF. At the routine blood test we found not known hyperthyroidism without detectable antibodies; thyroid ultrasound showed some cystic lesion without any nodule. Thyroid scintigraphy was normal. Antithyroid medications were started and one month later complete normalization of thyroid hormones occurred. The patient was event–free after correction of the hyperthyroidism. Discussion: "Happy heart syndrome" (HHS) is a TTS triggered by deep happiness and positive emotions. TTS is an usual form of acute cardiomyopathy characterized by reversible left ventricle apical ballooning which occurs in the absence of significant coronary artery disease. Although the exact cause of TTC remains unknown, several pathogenetic mechanisms have been suggested. Catecholamines seem to play a central role and we know that thyroid hormones interact with sympathetic nervous system so that hyperthyroidism is associated with hypersensitivity to catecholamines. Tako–Tsubo syndrome is usually triggered by negative stressors such as fright, grief, rage, other diseases. The role of positive emotions is not well known neither described. We assume that the mechanisms are similar but triggered by different emotions. HHS seems to be caused by pleasant emotional life events such as birthday party, son's wedding and so many others. Both positive and negative life events could trigger TTS, nevertheless negative life events trigger TTS in almost 95% of the cases, so "broken hearts" are more frequent than "happy hearts".